2000
DOI: 10.1128/jcm.38.3.1081-1084.2000
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Indirect Hemagglutination Assay for Diagnosis of Acute Leptospirosis in Hawaii

Abstract: Timely diagnosis of leptospirosis is important to ensure a favorable clinical outcome. The definitive serologic assay, the microscopic agglutination test (MAT), requires paired sera and is not useful for guiding early clinical management. The only screening test approved for use in the United States, the indirect hemagglutination assay (IHA), has not undergone extensive field evaluation. To assess the performance of the leptospirosis IHA in Hawaii, serum from patients evaluated for leptospirosis between 1992 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…The evaluation found that the EIE-IgM Leptospirose achieved similar performance characteristics as those reported for whole Leptospira-based serologic assays (Bajani et al, 2003, Effler et al, 2000, Levett and Branch, 2002, Sehgal et al, 2003, Smits et al, 2001a, Smits et al, 2001b, Vijayachari et al, 2002. This is not surprising for although the serovar source and preparation of antigen used in these assays may differ, they appear to detect an antibody response against the same immunodominant moiety, "broad reactive antigen" (Faine et al, 1999, Terpstra et al, 1985 which is expressed in the spectrum of pathogenic serovars.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…The evaluation found that the EIE-IgM Leptospirose achieved similar performance characteristics as those reported for whole Leptospira-based serologic assays (Bajani et al, 2003, Effler et al, 2000, Levett and Branch, 2002, Sehgal et al, 2003, Smits et al, 2001a, Smits et al, 2001b, Vijayachari et al, 2002. This is not surprising for although the serovar source and preparation of antigen used in these assays may differ, they appear to detect an antibody response against the same immunodominant moiety, "broad reactive antigen" (Faine et al, 1999, Terpstra et al, 1985 which is expressed in the spectrum of pathogenic serovars.…”
supporting
confidence: 57%
“…However these numbers significantly underestimate the true disease burden since (i) leptospirosis often goes unrecognized because of its non-specific presentation (Johnson et al, 2004, Murdoch et al, 2004, Russell et al, 2003, Segura et al, 2005, being misdiagnosed as dengue (Flannery et al, 2001, Karande et al, 2005, LaRocque et al, 2005, malaria (Ellis et al, 2006, Wongsrichanalai et al, 2003 or other causes of acute febrile illness, and (ii) standard diagnosis is based on antiquated methods, the microscopic agglutination test (MAT) and culture isolation, which are performed in few reference laboratories worldwide (Faine et al, 1999, WHO, 2003. Whole Leptospira-based serologic tests in ELISA and rapid formats are commercially-available and have a sensitivity of 28-72% and 75-94% to detect acute and convalescent-phase illness respectively (Bajani et al, 2003, Effler et al, 2000, Levett and Branch, 2002, Sehgal et al, 2003, Smits et al, 2001a, Smits et al, 2001b, Vijayachari et al, 2002. Limited access to effective diagnosis, especially in developing countries where the disease burden is greatest, is a major cause of under-reporting, which in turn has contributed to the perception of leptospirosis as a neglected disease.…”
mentioning
confidence: 99%
“…In these circumstances relatively simple assays such as the haemagglutination assay (Levett & Whittington 1998) may be used, but this assay has a limited sensitivity for samples collected early in the disease (Ef¯er et al 2000). Stability of assay reagents is an important prerequisite for tests used in tropical countries, and we recently described a dipstick assay (Gussenhoven et al 1997;Smits et al 1999;2000) and a latex agglutination test (Smit et al 2000b) for the detection of Leptospira-speci®c antibodies in human sera. The latex agglutination assay is performed by mixing on an agglutination card 5 ll serum with 5 ll antigen-coated, dyed latex beads.…”
Section: Introductionmentioning
confidence: 99%
“…However, laboratory facilities to perform such complicated and time‐consuming tests are rarely available in endemic areas. In these circumstances relatively simple assays such as the haemagglutination assay ( Levett & Whittington 1998) may be used, but this assay has a limited sensitivity for samples collected early in the disease ( Effler et al . 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…The wide geographic variability in infecting serogroups make interpretation of MAT results suspect without broad in‐depth knowledge of locally enzootic and endemic serogroups (Effler et al. 2000).…”
Section: Discussionmentioning
confidence: 99%